Epidemiological studies on leptospirosis in Chiang Mai (Thailand). - Arimitsu, Y. (Cambridge University Press, 1987)
A total of 270 serum samples collected in Chiang Mai province were examined for antibodies against leptospira using the microscopic agglutination test (MAT). Four of 40 serum specimens from patients who visited the hospital with the common cold, were positive with a titre of 20. Twelve (10.4%) of the 115 samples in the Doi Saket district showed a positive reaction. Only 2 of 115 sera of school children in Chiang Mai city had antibodies. Specific serovars detected were Leptospira hebdomadis (5), L. australis (3), L. icterohaemorrhagiae (2), L. bataviae (2), and one each of L. canicola, L. javanica and L. pyrogenes. One case of mixed infection with L. hebdomadis and L. javanica, and L. autumnalis and L. australis were observed.